2009
DOI: 10.1002/clc.20542
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anemia After Percutaneous Coronary Intervention on Clinical Outcomes

Abstract: Background: Although the consequences of bleeding after percutaneous coronary intervention (PCI) are well documented, there are no data on the impact of post-PCI anemia (PPA) on clinical outcomes. Methods: We evaluated the incidence, predictors, and prognostic implications of PPA on clinical outcomes in 1415 PCI procedures. We compared clinical outcomes of patients with PPA (ie, nadir post-PCI hemoglobin <10 gm/dL) vs without PPA. In patients with PPA, we assessed the influence of thrombolysis in myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
(15 reference statements)
2
27
0
Order By: Relevance
“…4,6,24 In our study, 1 in 5 patients who did not have baseline anemia (and did not undergo coronary bypass surgery) developed moderate to severe HAA.…”
Section: Commentmentioning
confidence: 91%
“…4,6,24 In our study, 1 in 5 patients who did not have baseline anemia (and did not undergo coronary bypass surgery) developed moderate to severe HAA.…”
Section: Commentmentioning
confidence: 91%
“…It has also been shown that a low postprocedural H and a periprocedural H drop ! 1 g/dl in patients undergoing percutaneous coronary intervention is associated with adverse outcomes [2,3]. The prognostic significance of baseline H in patients undergoing peripheral vascular interventions (PVI) is uncertain [4].…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8,11,12,[18][19][20][21] Recent studies have shown that clinically silent peri-procedural blood loss is strongly associated with increased mortality and contrast-induced nephropathy. 22,23 The predictors of a clinically silent or subclinical periprocedural drop in hemoglobin have not been defined. We performed a retrospective analysis of a large cohort of patients undergoing both coronary and peripheral vascular percutaneous interventions to identify predictors of a subclinical drop in hemoglobin.…”
Section: Introductionmentioning
confidence: 99%